Subretinal Delivery of Ultrathin Rigid-Elastic Cell Carriers Using a Metallic Shooter Instrument and Biodegradable Hydrogel Encapsulation - Stanzel, Boris V (ASSOC RESEARCH VISION OPHTHALMOLOGY INC, 2021)
10.1167/iovs.11-8260